Dari Perang Diponegoro Hingga Jalur Luna Maya : Potensi Wisata Di Puncak Kleco Kulon Progo - Pitaya (STIE Pariwisata API Yogyakarta, 2025)
The Puncak Kleco area in Duwet Hamlet, Purwoharjo Village, Samigaluh District, Kulon Progo Regency is known as a tourist attraction that has an attractive natural panorama. However, the landscape area of the Menoreh Hills has various other attractions, including a glimpse of history as a witness to the struggle of the Indonesian people against the colonialists. At one time in modern times the Puncak Kleco area also became a pop icon for bicycle sports tourism which was popularized by the Luna Maya Route. All of this represents significant potential for local communities to develop as a tourism product that can be packaged, implemented and developed by them. This research aims to carry out a potential inventory, identify attractions, map community participation and package tourism service products. The method used is observation, documentation, mapping, interviews and packaging in a total experience package model (mind, body, soul). The results show that the existing potential can be packaged easily by the community to make a product in the form of a simple tour package but provides a total experience for tourists. So it can be concluded that as a community-based tourist attraction, the Puncak Kleco area can synergize the potential of nature, history, culture and daily life of the local community in harmony.